7(2x+10)=6x+26+6x+4

Simple and best practice solution for 7(2x+10)=6x+26+6x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2x+10)=6x+26+6x+4 equation:


Simplifying
7(2x + 10) = 6x + 26 + 6x + 4

Reorder the terms:
7(10 + 2x) = 6x + 26 + 6x + 4
(10 * 7 + 2x * 7) = 6x + 26 + 6x + 4
(70 + 14x) = 6x + 26 + 6x + 4

Reorder the terms:
70 + 14x = 26 + 4 + 6x + 6x

Combine like terms: 26 + 4 = 30
70 + 14x = 30 + 6x + 6x

Combine like terms: 6x + 6x = 12x
70 + 14x = 30 + 12x

Solving
70 + 14x = 30 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
70 + 14x + -12x = 30 + 12x + -12x

Combine like terms: 14x + -12x = 2x
70 + 2x = 30 + 12x + -12x

Combine like terms: 12x + -12x = 0
70 + 2x = 30 + 0
70 + 2x = 30

Add '-70' to each side of the equation.
70 + -70 + 2x = 30 + -70

Combine like terms: 70 + -70 = 0
0 + 2x = 30 + -70
2x = 30 + -70

Combine like terms: 30 + -70 = -40
2x = -40

Divide each side by '2'.
x = -20

Simplifying
x = -20

See similar equations:

| a-95=25 | | gcf=42x+28y | | b-5+0.2b=-0.2 | | -8(7)+y=4 | | x^5-3x^4-x^3+3x^2=f(x) | | 2/3+3x+1/4=5/3 | | -8(3)+y=4 | | 3.2x-0.88+1.2=0 | | -8(-2)+y=4 | | 2(5x+4)+2=60 | | 4g-8=-20 | | X*2+5x+3=0 | | 2+3(5+5v)=62 | | 42x+28y=gcf | | -2(3y-4)-y=-4(y-2) | | 3(3x+2)=6(2x-3) | | 9x+3=7x-19 | | 2+15+15v=62 | | 40r^2-35r+16r-14=0 | | 50m+42750=42675-175m | | 4(2x-7)=3(x-1) | | 5y+35=x+5 | | G(10)=50 | | 7x-47=x | | G(7)=98 | | 8x+23=3x+128 | | 20(-2+x)+10=50(-1+4x) | | 8x-10=7x-5 | | F(4)=96 | | V^2+(6.6V)-51.48=0 | | a-152= | | y+.5= |

Equations solver categories